(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2016)
An investigation was carried out to analysis the genetic diversity of 12 Bangladeshi local Boro rice (Oryza sativa L.) germplasm using morphological traits and molecular markers. Eight morphological traits (viz., days to 50 percent flowering, growth duration, plant height, filled grain/panicle, 1000 grain weight and grain yield) and eight Simple Sequence Repeat (SSR) markers were used for this analysis. The plant morphological traits exhibited more variation among the genotypes tested. Several traits were found to be significantly positive in correlation coefficient analysis and thus those traits can be considered stable as demonstrated by their coefficient of variability. A set of eight SSR primer pairs was used for molecular characterization resulting 49 alleles, where average of allele number was 6.13. The polymorphic information content (PIC) values ranged from 0.67 (RM1) to 0.86 (RM314) with an average of 0.76. The highest PIC value (0.86) was obtained for RM314 which also gave maximum alleles. The PIC value revealed that RM314 was the best marker for 12 genotypes tested. The cluster analysis based on UPGMA system grouped 12 genotypes into four clusters.